Efficacy of ultraviolet light-emitting diodes (UV-LED) at four different peak wavelengths against Cryptosporidium parvum oocysts by inactivation assay using immunodeficient mice. (August 2020) - Takahashi, Karin; Matsubayashi, Makoto; Ohashi, Yukio; Naohara, Jun; Urakami, Itsuo; Sasai, Kazumi; Kido, Yasutoshi; Kaneko, Akira; Teramoto, Isao
Abstract: As an alternative to using ultraviolet (UV) lamps, which are made with mercury that is toxic to the environment and human health, UV light-emitting diodes (UV-LEDs) are expected to be effective for inactivating microorganisms in water. Although UV-LEDs have been reported to be effective against bacteria and viruses, the effectiveness of UV-LEDs against Cryptosporidium parasites has not been fully evaluated. As we report here, we have developed an in vivo quantitative inactivation assay for C. parvum oocysts using immunodeficient mice. Using the assay, we evaluated the effectiveness of treatment by UV lamp (254 nm) at approximately 1000 μJ/cm 2 (for 3 s at a distance of 95 mm) compared to inactivation by commercially available UV-LEDs (with peak wavelengths of 268, 275, 284, and 289 nm). The shed patterns of oocysts after treatment with 284- and 289-nm wavelength UV-LEDs were significantly delayed compared to that after treatment with a UV lamp. These findings provide the first suggestion that UV-LEDs are effective against these parasites, as assessed using commercially available 350-mA UV-LEDs under conditions of fixed exposure distance and time. Graphical abstract: Unlabelled Image Highlights: Among UV-LEDs of 268–289 nm, the inactivation rate for the 284 and 289-nm UV-LED was the highest. These findings provide the first suggestion that UV-LEDs are effective against these parasites. As an alternative to UV lamps, UV-LEDs can be useful for inactivating microorganisms in water.